2022
DOI: 10.4093/dmj.2021.0258
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Body Mass Index Variability and Incident Diabetic Microvascular Complications: A Post Hoc Analysis of ACCORD Trial

Abstract: Background: Obesity is associated with adverse health events among diabetic patients, however, the relationship between obesity fluctuation and risk of microvascular complications among this specific population is unclear. We aimed to examine the effect of waist circumference (WC) and body mass index (BMI) variability on the risk of diabetic microvascular outcomeMethods: Annually recorded anthropometric data in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study was used to examine the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…As an essential risk factor for various diseases, a meta-analysis of MR studies showed that BMI has causal associations with T2D, aortic valve stenosis, heart failure, stroke, peripheral artery disease, death due to chronic obstructive pulmonary disease (COPD), and kinds of tumors 15. Observational studies also confirm that BMI increases the risk of T2D and raises the risk of microvascular and cardiovascular complications in diabetes 16–18…”
Section: Discussionmentioning
confidence: 98%
“…As an essential risk factor for various diseases, a meta-analysis of MR studies showed that BMI has causal associations with T2D, aortic valve stenosis, heart failure, stroke, peripheral artery disease, death due to chronic obstructive pulmonary disease (COPD), and kinds of tumors 15. Observational studies also confirm that BMI increases the risk of T2D and raises the risk of microvascular and cardiovascular complications in diabetes 16–18…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the Action for Health in Diabetes (Look AHEAD) trial in the US reported that fluctuations in BMI over a 4-year period were associated with adverse outcome in the control group but not in the intensive lifestyle intervention group [ 10 ]. Little data exist with regard to the relationship between fluctuations in BMI and cancer mortality or microvascular disease, but Chang et al [ 11 ] recently reported that fluctuations in BMI were associated with increased risk of hepatocellular carcinoma in the general population, whilst a post hoc analysis of the ACCORD trial found that fluctuations in BMI in subjects with type 2 diabetes were associated with increased risk of renal events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the keen interest of Dr. Yun Kyung Cho in our published article, “Waist circumference and body mass index variability and incident diabetic microvascular complications: a post hoc analysis of ACCORD trial,” [ 1 ] and are also grateful for the opportunity to further discuss our work.…”
mentioning
confidence: 99%